Reversed Phase Extraction Chromatographic Studies of Zinc, Cadmium and Mercury - Aher, H.R.; Kuchekar, S.R. (Asian Journal of Chemistry, 2016)
A reversed phase paper chromatographic method is developed for separation of zinc, cadmium and mercury. The separations have been performed on a Whatman paper No. 1 using liquid ion exchanger n-octylaniline and N-n-octylaniline as a stationary phase while various weak acids as the mobile phase. Various experiments were carried out to study the effect of pH (4-9), concentration of mobile phase (0.01-0.1 M) and concentration of stationary phase (0.1-1.5% using chloroform as a diluent) on the Rf values of individual cations. Optimum concentration of n-octylaniline, N-n-octylaniline and mobile phases were determined. The proposed method is applied for separation and detection of zinc, cadmium and mercury in pharmaceutical samples.